2001
DOI: 10.1053/joca.2000.0345
|View full text |Cite
|
Sign up to set email alerts
|

Effects of an orally administered mixture of chondroitin sulfate, glucosamine hydrochloride and manganese ascorbate on synovial fluid chondroitin sulfate 3B3 and 7D4 epitope in a canine cruciate ligament transection model of osteoarthritis

Abstract: Administration of CS-G-M was associated with altered concentrations of 3B3 and 7D4 epitope in synovial fluid, suggesting that these compounds may act to modulate articular cartilage matrix metabolism in vivo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
53
0
3

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(56 citation statements)
references
References 40 publications
0
53
0
3
Order By: Relevance
“…It has been suggested to restore the extracellular matrix of cartilage, reducing degradation in OA, and provide sulphur-containing amino acids that are essential for the cartilage extra-cellular matrix, which may be deficient from regular diets [24,25]. A systematic review of chondroitin found that chondroitin had small to moderate effects on pain and physical function in patients with OA, which were clinically significant [26].…”
Section: Chondroitinmentioning
confidence: 99%
“…It has been suggested to restore the extracellular matrix of cartilage, reducing degradation in OA, and provide sulphur-containing amino acids that are essential for the cartilage extra-cellular matrix, which may be deficient from regular diets [24,25]. A systematic review of chondroitin found that chondroitin had small to moderate effects on pain and physical function in patients with OA, which were clinically significant [26].…”
Section: Chondroitinmentioning
confidence: 99%
“…A negative-controlled study conducted by Johnson and others (2001) tested the effects of a supplement containing 200 mg CS, 250 mg GH, and 5 mg manganese ascorbate per capsule in dogs who underwent cranial cruciate ligament transection (n = 16). Dogs were given 3 capsules every 12 hours for 30 days before the dose was reduced to 2 capsules every 12 hours for the following 4 months (Johnson et al, 2001). Compared to the controls, dogs given the supplement had elevated concentrations of CS epitopes in synovial fluid, suggesting modulation of articular cartilage matrix metabolism (Johnson et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Dogs were given 3 capsules every 12 hours for 30 days before the dose was reduced to 2 capsules every 12 hours for the following 4 months (Johnson et al, 2001). Compared to the controls, dogs given the supplement had elevated concentrations of CS epitopes in synovial fluid, suggesting modulation of articular cartilage matrix metabolism (Johnson et al, 2001). A doubleblind, placebo-controlled study conducted using arthritic dogs (n = 7 to 10/treatment group) noted a reduction in observational pain overall (51%), after limb manipulation (48%), and after physical exertion (43%) after 150 days of supplementation of 2000 mg GH and 1600 mg CS (P < 0.05) (Gupta et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Osteoarthritis is a slowly progressive, degenerative, and debilitating disease affecting 20% of the canine population over the age of one (Johnston, 1997;Johnson et al, 2001;Roush et al, 2002;Aragon et al, 2007). Large-breed dogs may develop more severe clinical signs and initial symptoms of osteoarthritis; however, dogs of all sizes and breeds are affected by the disease as they age (Rychel, 2010).…”
Section: Introductionmentioning
confidence: 99%